2009
DOI: 10.1140/epjd/e2009-00164-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation instability induced by periodic power variation in soliton fiber ring lasers

Abstract: Modulation instability with subsideband generation induced by periodic power variation in soliton fiber ring lasers is reported. We found that different wavelength shifts of subsideband generation are related to different periodic power variation. The period of power variation and wavelength shifts of subsideband can be changed by altering the linear cavity phase delay. It is also found that the periodic power variation is caused by the interaction between the nonuniform polarization state of the circulating l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…The nonlinearity is enhanced by the reGO flakes deposited on the 8 mm taper waist. The threshold is decreased by the periodic dispersion and loss variations experienced by pulses circulating in the cavity [15][16][17]. The corresponding optical spectrum for ML under XPMI shown in Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nonlinearity is enhanced by the reGO flakes deposited on the 8 mm taper waist. The threshold is decreased by the periodic dispersion and loss variations experienced by pulses circulating in the cavity [15][16][17]. The corresponding optical spectrum for ML under XPMI shown in Fig.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…To decrease the MI threshold, researchers have focused on MI in fibers with periodical variations of dispersion or nonlinearity [11][12][13][14], and MI in fiber resonators, where parametric gain is increased due to accumulated nonlinearity experienced by pulses circulating in laser cavity [15][16][17]. Haelterman et al show that MI could occur in a fiber ring resonator with normal dispersion, where the phase matching was obtained by the coupling between two polarization components [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, the nonlinear polarization rotation (NPR) technique acting as an artificial saturable absorber is used extensively to achieve Q‐switched [8] and mode‐locked [9–12] pulses in fiber lasers. Optical components in the laser cavity go through the intensity dependent loss caused by the polarizer combining with the linear and nonlinear phase shift of orthogonally polarized modes.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral effects caused by MI in the soliton fiber ring lasers have been reported elsewhere, which were characterized by subsideband generation. It was shown that MI with subsideband generation in the fiber ring lasers could be caused by the periodic dispersion variation [21] and periodic power fluctuation [22]. The MI discussed above occurs in the fiber lasers with only single wavelength operation.…”
Section: Introductionmentioning
confidence: 99%